2020
DOI: 10.1038/s41598-020-72703-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic hypothermia after cardiac arrest increases the plasma level of B-type natriuretic peptide

Abstract: Natriuretic peptides (NPs) regulate blood pressure and fluid homeostasis and exert various effects on the cardiovascular system. Recently, the relationship between NPs and the energy metabolism has been reported, and using a cell culture experiment system, we previously showed that NP activated brown cells in a low temperature environment while also suppressing a decrease in the cell temperature. However, few reports have described the secretion of NPs in cold environments, and there have been almost no studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
(58 reference statements)
3
7
0
Order By: Relevance
“…We found that circulating NPs levels are elevated during cold exposure, which is consistent with the ndings of previous studies, including our own [6,7,10]. Several possible mechanisms have been proposed.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found that circulating NPs levels are elevated during cold exposure, which is consistent with the ndings of previous studies, including our own [6,7,10]. Several possible mechanisms have been proposed.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, our clinical study using the cardiac catheter database showed that an impaired cardiac function is associated with a decrease in body temperature, whereas plasma BNP elevation is associated with an increase in body temperature, suggesting the adaptive heat-retaining property of NP when the body temperature falls owing to unfavorable hemodynamic conditions [4]. Conversely, it has also been reported in both experimental [6,7] and clinical [10] studies that cold exposure induces the elevation of NP levels, which supports the idea that NPs induce the activation of the adipose tissue thermogenic program in response to cold stimuli as a compensatory mechanism [5,14]. A series of these studies indicated that NPs play a central role in "myocardial-adipose crosstalk".…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…8,9 In addition to the classical actions of hemodynamic regulation, growing evidence suggests that NPs also regulate energy balance and glucose homeostasis as well as thermogenesis through interorgan metabolic crosstalk with adipose tissue, in which NP receptors are expressed (Figure). [8][9][10][11][12][13] Recent studies have shown that NPs stimulate triglyceride lipolysis and promote the uncoupling of mitochondrial respiration through induction of adipose tissue browning, which results in improved insulin resistance as well as activation of the thermogenic program. 10-12, 14 In fact, we recently reported that an increase in BNP level improves insulin resistance and promotes glucose utilization, particularly in patients with acute coronary syndrome, in which glucose is the preferred substrate for energy metabolism.…”
mentioning
confidence: 99%
“…However, it is currently believed that NPs have a variety of other effects. Recently, many researchers have focused on the relationship between NPs and energy metabolism 16 18 , and we reported several investigations about this relationship 19 23 . However, in patients with cardiovascular disorders, the direct relationship between NPs and ketone bodies has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 96%